PENGEMBANGAN MEDIA PEMBELAJARAN BETANG EDU BERBASIS ANDROID PADA MATERI TOLERANSI DAN MENGHARGAI PERBEDAAN - Nova Nur Aini; Muhammad Rifaldi; Afda Yulistiana; Abdul Azis (CV. ADIBA AISHA AMIRA, 2024)
The development of mobile technology opens up opportunities for innovation in Islamic Religious Education (PAI) learning, especially in the material of tolerance and respect for differences. This research aims to develop and test the feasibility of the Android-based learning media